The Impact of the COVID-19 Pandemic on Consumer Bankruptcies - Hackney, Donald D.; Friesner, Daniel L. (Journal of Applied Business and Economics, 2021)
This manuscript conducts a simple, exploratory analysis to test whether the use of the consumer bankruptcy process fundamentally differed during the COVID-19 pandemic compared to previous years. Data were drawn from the Public Access to Court Electronic Records (PACER) database maintained by the U.S. Bankruptcy Court’s Eastern District of Washington for the years 2007, 2011, 2016, and 2020. KruskalWallis tests indicate that filers in 2020 had lower average real monthly incomes than in previous years. However, household incomes were not statistically different from previous years. Filers in 2020 has significantly more debt in collections compared to 2007, but no more or less debt than in 2011 or 2016. Chi-square tests report a significantly greater proportion of filings with debts owed to collections agencies in 2020 compared to previous years. Overall, the findings suggest that the pandemic did significantly alter the use, and intensity of use, of the consumer bankruptcy process.